Clinical pharmacy interventions in paediatric electronic prescriptions. Issue 3 (26th November 2012) - Maat, Barbara; Au, Yuen San; Bollen, Casper W; van Vught, Adrianus J; Egberts, Toine C G; Rademaker, Carin M A
Abstract : Objective: To examine the frequency, nature and determinants of clinical pharmacy interventions in paediatric electronic prescriptions. Design: Prospective cohort with nested case–control study. Setting: Tertiary children's hospital, The Netherlands. Patients: Patients 0–18 years with at least one drug prescription admitted to hospital between 1 March 2004 and 1 January 2008, excluding patients receiving intensive care. Interventions: Electronic medication prescriptions for paediatric inpatients were verified and if necessary interventions were made by the paediatric clinical pharmacy. Prescriptions requiring intervention (cases) were compared with prescriptions not requiring interventions (controls). Main outcome measures: Frequency of clinical pharmacy interventions, per 10 000 paediatric electronic prescriptions, and the determinants thereof. Results: Interventions were made for 1577 (1.1%) of 138 449 prescriptions. 81% of the interventions concerned correction of a prescription that might have had adverse clinical consequences. Interventions in prescriptions for antibacterial agents for systemic use were made most often. Most corrections concerned wrong doses (45%). 1577 cases were compared with 1983 controls. The risk of interventions was higher for children aged 1 month to 2 years than for 12–18-year-olds (OR=1.97 (95% CI 1.63 to 2.38)). The risk for 'free-text' prescriptions was five times higher than for 'standardised structured template' prescriptions. No differences were found between day, evening and night shift prescriptions. Significantly more interventions were made in the oral dosage form (OR=1.63 (95% CI 1.41 to 1.88)) and administration route (OR=1.80 (95% CI 1.55 to 2.09)) than for other reasons. Conclusions: Paediatric prescribing errors occur frequently and are not completely prevented by electronic prescribing systems. This study provides information for improvements in electronic prescribing for paediatric patients. Incorporating tailored solutions, such as minimised free-text entry, certain obligatory fields and integrated dose checking and indications, can improve the quality and efficiency of electronic prescribing in paediatrics.